Controlling soil-borne fungus aspergillus niger in groundnut by optimizing the function of isolated bacillus bacteria - Hieu, Nguyen Xuan; Huy, Nguyen Duc; Long, Nguyen Tien; Thuyet, Cao Thi; Hoai, Pham Thi Thuy; Thuy, Nguyen Thi Thu (Penerbit Universiti Kebangsaan Malaysia, 2024)
Collar rot is a devastating disease caused by the soil-borne pathogen Aspergillus niger that greatly affects groundnut production worldwide. The long-term persistence of the fungus in the soil can reduce the effectiveness of synthetic fungicides. Recently, significant attention has been raised to the use of the biological control method such as the application of antagonistic microorganisms, which potentially decline the number of spores and eradicated A. niger from the soil. In the present study, three Bacillus strains (Bacillus siamensis 101, B. siamensis 112 and B. velezensis 137) isolated from the rhizosphere soil of groundnut cultivation farms were found to inhibit the growth of A. niger mycelia by 53.6% to 60.8% in vitro. In pot experiments, the supplementation of this mixture of three bacterial strains (namely BAZ04) strongly reduced the collar rot symptoms of groundnut with a biocontrol efficacy of 100% compared to nil (no treatment). Field trials demonstrated the efficiency of BAZ04 in controlling collar rot disease, which increased the yield by 20.5–22.7% compared to the untreated plots. These results suggest that BAZ04 is a potential biocontrol agent for collar rot disease.